Strategic Choices for Redistribution and the Veil of Ignorance: Theory and Experimental Evidence - Anke Gerber; Andreas Nicklisch; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2013)
We provide experimental evidence on the emergence of redistributive societies. Individuals first vote on redistribution by feet and then learn their productivity and invest. We vary the individuals' information about their productivities at the time when they choose a distribution rule and find that there is more redistribution behind a veil of ignorance than under full information. However, the scope of redistribution is less sensitive towards the degree of uncertainty than predicted. For all degrees of uncertainty, we find a coexistence of libertarianism and redistribution as well as incomplete sorting, so that heterogeneous redistribution communities turn out to be sustainable.
Keywords: C91; D02; D63; H24; K00; 330; constitutional choice; experimental economics; redistribution; veil of ignorance; voting by feet